Colonial Jerusalem : The Spatial Construction of Identity and Difference in a City of Myth, 1948-2012 - Abowd, Thomas Philip, 1967- (Book collections on Project MUSE., 2014)
This anthropological work draws on recent theories about racial politics, colonialism, and urban spatial dynamics to examine social segregation in Jerusalem. The author examines the physical manifestations--walls, checkpoints, and separate road networks-- as well as myths, memorials, and monuments in the "Jerusalem of Israel's imagination," national boundaries, gendered politics of residential life, terrorism, policing, and the demolishing of homes and buildings.